Engineering Nonvolatile Polarization in 2D α-In2Se3/α-Ga2Se3 Ferroelectric Junctions - Peipei Li; Delin Kong; Jin Yang; Shuyu Cui; Qi Chen; Yue Liu; Ziheng He; Feng Liu; Yingying Xu; Huiyun Wei; Xinhe Zheng; Mingzeng Peng (Nanomaterials)
The advent of two-dimensional (2D) ferroelectrics offers a new paradigm for device miniaturization and multifunctionality. Recently, 2D α-In2Se3 and related III–VI compound ferroelectrics manifest room-temperature ferroelectricity and exhibit reversible spontaneous polarization even at the monolayer limit. Here, we employ first-principles calculations to investigate group-III selenide van der Waals (vdW) heterojunctions built up by 2D α-In2Se3 and α-Ga2Se3 ferroelectric (FE) semiconductors, including structural stability, electrostatic potential, interfacial charge transfer, and electronic band structures. When the FE polarization directions of α-In2Se3 and α-Ga2Se3 are parallel, both the α-In2Se3/α-Ga2Se3 P↑↑ (UU) and α-In2Se3/α-Ga2Se3 P↓↓ (NN) configurations possess strong built-in electric fields and hence induce electron–hole separation, resulting in carrier depletion at the α-In2Se3/α-Ga2Se3 heterointerfaces. Conversely, when they are antiparallel, the α-In2Se3/α-Ga2Se3 P↓↑ (NU) and α-In2Se3/α-Ga2Se3 P↑↓ (UN) configurations demonstrate the switchable electron and hole accumulation at the 2D ferroelectric interfaces, respectively. The nonvolatile characteristic of ferroelectric polarization presents an innovative approach to achieving tunable n-type and p-type conductive channels for ferroelectric field-effect transistors (FeFETs). In addition, in-plane biaxial strain modulation has successfully modulated the band alignments of the α-In2Se3/α-Ga2Se3 ferroelectric heterostructures, inducing a type III–II–III transition in UU and NN, and a type I–II–I transition in UN and NU, respectively. Our findings highlight the great potential of 2D group-III selenides and ferroelectric vdW heterostructures to harness nonvolatile spontaneous polarization for next-generation electronics, nonvolatile optoelectronic memories, sensors, and neuromorphic computing.